PENDAMPINGAN MANAJEMEN USAHA KECIL PADA KELOMPOK SRIKANDI GUNA PENINGKATAN PENGHASILAN KELUARGA - Widajanti Erni; Sumaryanto Sumaryanto (STIE PGRI Dewantara Jombang, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are one of the sectors that are the foundation of the economy in Indonesia. The condition was proven during the Covid-19 pandemic; there were still many MSMEs that were able to survive and become one of the family's economic boosters. Despite their significant role, many problems are faced by MSMEs in Indonesia, including limited capital, business management, and marketing of production results. This Community Service activity aims to help women members of the Srikandi MSME group as fostered partners so the business can be marketed better. The activity was conducted in Gilingan Village, Banjarsari District, Surakarta Municipality. This activity was carried out intensively and received a positive response from the fostered partners. From the activity results, partners gain meaningful insight into entrepreneurship. Encouraged partners also receive guidance on managing their business and marketing concepts to increase sales volume and get maximum profits.